2022
DOI: 10.3390/jcdd9110366
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Treatment and Its Association with Outcome in a Multicenter Cohort of Transcatheter Edge-to-Edge Mitral Valve Repair Patients

Abstract: Transcatheter edge-to-edge mitral valve repair (TEER) has become established as a safe and efficacious therapy for severe mitral regurgitation (MR) in high-risk patients. Despite its widespread use, postprocedural antithrombotic therapy (ATT) still to date is based on local expertise rather than evidence. In a multicenter, observational cohort study, 646 consecutive patients undergoing TEER were enrolled; 609 patients were successfully treated and antithrombotic therapy analyzed; 449 patients (73.7%) were prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For this particular high-risk cohort, transcatheter edge-to-edge repair (TEER) has proven to be a safe and beneficial treatment modality, alleviating HF symptoms (5) and even improving prognosis in selected MR etiologies (6,7). With a prevalence of up to 75.4% (8), atrial fibrillation (AF) is the most common comorbidity in TEER collectives and, as demonstrated in a multitude of recent studies, dramatically worsens the medium-and long-term outcome of successfully treated TEER patients (9)(10)(11)(12)(13). In contrast to the collective of surgically treated MR patients, in whom there is convincing evidence of prognostically favorable concomitant rhythm control of AF (14), reflected in a class I-A recommendation in the relevant guideline (15), the evidence in TEER patients regarding the prognostic impact of AF treatment regimens is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For this particular high-risk cohort, transcatheter edge-to-edge repair (TEER) has proven to be a safe and beneficial treatment modality, alleviating HF symptoms (5) and even improving prognosis in selected MR etiologies (6,7). With a prevalence of up to 75.4% (8), atrial fibrillation (AF) is the most common comorbidity in TEER collectives and, as demonstrated in a multitude of recent studies, dramatically worsens the medium-and long-term outcome of successfully treated TEER patients (9)(10)(11)(12)(13). In contrast to the collective of surgically treated MR patients, in whom there is convincing evidence of prognostically favorable concomitant rhythm control of AF (14), reflected in a class I-A recommendation in the relevant guideline (15), the evidence in TEER patients regarding the prognostic impact of AF treatment regimens is limited.…”
Section: Introductionmentioning
confidence: 99%
“…AF is not uncommon comorbidity in patients with moderate or severe MR as showed in the large registries Real World Expanded Multi-center Study of the MitraClip System (REALISM) [ 31 ] and A Two-Phase Observational Study of the MitraClip System in Europe (ACCESS-EU) [ 32 ] which report coexisting AF in 66.5% and 67.7% of TEER patients, respectively. A recent multicenter, observation study, showed that the prevalence of concomitant AF in patients who underwent TEER was more than 75% and the majority of patients received postprocedural antithrombotic therapy consisting of an oral anticoagulant [ 33 ]. Overall, VKAs were used most frequently compared with DOACs (52.1% vs. 47.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Post-procedurally, in patients with indication for OAC, the combination of OAC + SAPT was used most frequently (55.2%), followed by OAC monotherapy (32.6%) and OAC + DAPT combination (12.2%). The remaining patients without an indication for OAC (26.3%) received ASA pre-procedurally (88.7%) and were predominantly switched to DAPT with the addition of clopidogrel after TEER (82.5%) [ 33 ]. Current practice for patients with AF and a clear indication for lifelong OAC is to maintain OAC with VKA and a target international normalized ratio (INR) 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Data from "real-world" registries and meta-analyses show bleeding rates within the first 30 days from 2.0% to 13.4%. [15][16][17][18] The higher bleeding rate of 21% observed in our study may be related to the use of OAC in all patients, differences in bleeding definitions but also to the review of the patient files to check a drop in haemoglobin and need for transfusion, minimizing the risk of underreporting.…”
Section: Discussionmentioning
confidence: 99%